Biocontrol efficacy of Bacillus velezensis strain YS-AT-DS1 against the root-knot nematode Meloidogyne incognita in tomato plants - Hu, Yanfeng; You, Jia; Wang, Yu; Long, Yong; Wang, Siru; Pan, Fengjuan; Yu, Zhenhua (Frontiers in Microbiology, 2022)
Root-knot nematodes (RKNs; Meloidogyne spp.), one of the most economically important plant-parasitic nematodes (PPNs), cause severe yield and quality losses in agriculture annually. The application of biological control agents is an environmentally safe and effective approach to control RKNs. Here, we report the genomic characteristics of a Bacillus velezensis strain YS-AT-DS1 (Bv-DS1) isolated from the tidal soil, revealing that it has a 4.73 Mb circular chromosome with an average GC-content of 46.43%, 3,977 genes, 86 tRNAs, and 27 rRNAs, and contains secondary metabolite clusters for producing antimicrobial compounds. In vitro assays indicated that Bv-DS1 has not only antagonistic activities against fungal pathogens, but also shows nematicidal activity, with a mortality rate of 71.62% mortality rates in second-stage juvenile (J2s) Meloidogyne incognita. We then focused on the biocontrol efficiency of Bv-DS1 against M. incognita in pot assays. Preinoculation with Bv-DS1 enhanced tomato growth, and significantly reduced the infection rate of J2s, and the number of galls and egg masses on tomato roots. The underlying mechanism in Bv-DS1-induced resistance to M. incognita was further investigated through split-root experiments, and analysing the expression of the genes related to jasmonic acid (JA), salicylic acid (SA), and the tonoplast intrinsic protein (TIP). The results indicated that Bv-DS1 could not activate host systemic-induced resistance (ISR) in the split-root system of tomatoes. Additionally, the expression of JA- (LOX D and MC) and SA- (PAL2 and PR) responsive genes did not change in Bv-DS1-pretreated plants at 3 and 14 days after nematode inoculation. The presented data showed that JA- and SA-dependent pathways were not required for the biocontrol action of the Bv-DS1 against RKN. The TIP genes, responsible for transport of water and small substrates in plants, have previously been shown to negatively regulate the parasitism of PPNs. Surprisingly, Bv-DS1 compromised the downregulation of TIP1.1 and TIP1.3 by M. incognita. Together, our data suggest that Bv-DS1 exhibits a dual effect on plant growth promotion and protection against RKN, possibly related to the regulation of water and solute transport via TIPs. Thus, the Bv-DS1 strain could be used as a biocontrol agent for RKN control in sustainable agriculture.